Pemilihan Kepala Daerah Yang Demokratis Dalam Perspektif UUD 1945 - Nopyandri ' (Jurnal Ilmu Hukum, 2010)
Direct election of regional heads have taken place sinceyear 2005, that relied on by rule of UU of Number 32Year 2004 with have base of rule section 18 article 4Constitusional 1945. Inescapable fact in direct localelections in stages capitalization is emerging localelections that were far more expensive than the modelof local elections by Parliament representatives as wellas the nuances of the most notable is the rise of localelection dispute is submitted to the ConstitutionalCourt. Policy of the government and Parliamentthrough Law No. 32 of 2004 which further amendedby Act No. 12 of 2008 specifies that local elections areconducted in direct elections should be viewed as apolitical fact local election law.